Comparison of the Pharmacokinetic Properties of Naloxone Following the Use of FDA‐Approved Intranasal and Intramuscular Devices Versus a Common Improvised Nasal Naloxone Device. (12th March 2019) - Krieter, Philip A.; Chiang, C. Nora; Gyaw, Shwe; McCann, David J.
Abstract: For more than a decade, first responders and the general public have been able to treat suspected opioid overdoses using an improvised nasal naloxone device (INND) constructed from a prefilled syringe containing 2 mg of naloxone (1 mg/mL) attached to a mucosal atomization device. In recent years, the U.S. Food and Drug Administration (FDA)–approved Ezvio, an autoinjector that delivers 2 mg by intramuscular injection and Narcan nasal spray (2‐ and 4‐mg strengths; 0.1 mL/dose) for the emergency treatment of a known or suspected opioid overdose. The present study was conducted to compare the pharmacokinetics of naloxone using the FDA‐approved devices (each administered once) and either 1 or 2 administrations using the INND. When naloxone was administered twice using the improvised device, the doses were separated by 2 minutes. The highest maximum plasma concentration was achieved using the 4‐mg FDA‐approved spray. The highest exposures at 5 minutes postdose, based on AUC values, were after administration with the autoinjector and the 4‐mg FDA‐approved spray; at 10, 15, and 20 minutes postdose, the latter yielded the greatest exposure. Even after 2 administrations, the INND failed to achieve naloxone plasma levels comparable to the FDA‐approved devices at any time. The ease of use and higher plasma concentrations achieved using the 4‐mg FDA‐approved spray, compared with the INND, should be considered when deciding which naloxone device to use.